Alleviating isolation stress in chickens: The benefits of home pen playback and mirrors - Janja Sirovnik (PLoS ONE, 2025)
This study investigated whether the provision of (1) a mirror or (2) video and sound playback of conspecifics in the home pen (i.e., playback) could alleviate stress in socially isolated adult domestic chickens. Thirty adult chickens participated in the study, undergoing three-minute sessions of social isolation over three consecutive days in an arena containing a tray of food treats. Each chicken was exposed to three conditions, one per day, in a semi-randomised order: (1) mirror, (2) playback, and (3) control. Video recordings of the tests were coded for stress-related behaviours, including stress behaviour (i.e., pooled stress vocalisations and escape behaviour), vigilance, feeding, and exploration. Additionally, thermal imaging was used to measure the surface temperatures of the eye and comb. Social isolation elicited mild stress responses, as evidenced by reduced surface eye and comb temperatures along with the exhibition of stress and vigilance behaviours. Both playback and mirror conditions appeared to reduce stress behaviours compared to the control, although the effect of the mirror was not statistically significant. It is possible that the playbacks simulated the presence of a group of calm conspecifics. Vigilance behaviour, however, remained unaffected across conditions. These findings suggest that playback, and to a lesser extent mirrors, may alleviate certain stress-related behaviours in socially isolated adult chickens. As individual variation was high, future research should explore the role of individual differences in stress responses, as well as the long-term effects of repeated exposure to mirrors and playback, along with other environmental variables.